Coated copper-based composite coating material as well as preparation process and application thereof

By using a clad copper-based composite coating material on wind-powered sliding bearings, combined with ball milling technology and nickel coating technology, a synergistic lubrication effect is formed, which solves the problems of poor self-lubricating performance and low bonding strength of sliding bearings, and significantly improves service life and reliability.

CN119703069AActive Publication Date: 2025-03-28CHONGQING WANGJIANG IND
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411984427.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Wind power sliding bearings have poor self-lubricating performance under complex working conditions and low combined strength, resulting in increased friction and intensified wear, shortened service life, and reduced reliability and operating efficiency.

Method used

The coated copper-based composite coating material is used to uniformly disperse a variety of lubricating phases, such as graphite, polystyrene grease, bentonite, CaF2, and MoS2, through the ball milling process, forming a synergistic lubricating effect, and the lubricating phase is protected by nickel coating technology to avoid decomposition. Ultra-high-speed laser cladding technology is used to form coatings to ensure bond strength and lubricating properties.

Benefits of technology

The self-lubricity and bonding strength of the sliding bearing are significantly improved, the friction coefficient is reduced to 0.15, the bonding strength reaches 250MPa, the service life is doubled, and there are no problems such as coating peeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703069A_ABST
    Figure CN119703069A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wind power bearing lubrication, and discloses a coated copper-based composite coating material and a preparation technology and application thereof.The coated copper-based composite coating material comprises 60-80% of aluminum bronze or tin bronze powder and 20-40% of a lubricating phase, and the lubricating phase is formed by mixing at least two kinds of powder of graphite, polybenzoate, bentonite, CaF2 and MoS2. According to the invention, a multi-component lubricating phase is adopted to play a synergistic lubricating role, so that the self-lubricating property of the coating is obviously improved, and the friction coefficient is reduced; the lubricating phase is coated with the copper-based alloy powder, so that decomposition of the lubricating phase in the ultra-high-speed laser cladding process is avoided, the functionality of the lubricating phase is guaranteed, and the service life of the coating is remarkably prolonged; the technical problems that in the wind power field, an existing sliding bearing is poor in self-lubricating performance and low in bonding strength are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wind power bearing lubrication, and in particular to a coated copper-based composite coating material, a preparation process and an application thereof. Background Art

[0002] In the field of modern wind power generation, wind turbine bearings, as key components, play a vital role in the stable operation of the entire wind power system. However, the current wind turbine main shaft bearings and gearbox bearings mostly rely on imported rolling bearings. This situation has, to a certain extent, restricted the independent and controllable development of my country's wind power industry. Gearbox bearings require high reliability, long operating time (20 to 25 years), smooth operation, low noise, small size, light weight, and cannot be replaced during the life cycle (the replacement cost exceeds the overall gearbox cost).

[0003] Rolling bearings have a dominant position in wind power practice due to their significant advantages such as standardized size, convenient selection, stable quality and good interchangeability, but they also have the disadvantages of limited service life and large size. In contrast, sliding bearings are gradually emerging with their low cost and high reliability. In the application scenario of wind power gearbox bearings, the advantages of sliding bearings are particularly prominent, and their corresponding market size will also grow rapidly.

[0004] However, wind turbine sliding bearings face extremely special and complex environments during operation. On the one hand, wind turbines are usually installed outdoors, whether on land or at sea, and must withstand the test of various harsh weather conditions; on the other hand, the vibration and impact generated during the operation of wind turbines also put forward higher requirements for the lubrication of sliding bearings. At present, in addition to adding copper sleeves to sliding bearings, copper-based alloy coatings are also prepared on the surface of sliding bearings by laser cladding; when copper sleeves or copper-based alloys are used as surface lubricating coatings, the lubrication effect is generally poor, and it is often necessary to prepare a polymer lubricating layer on the surface. However, adding a polymer lubricating layer will inevitably increase the coating preparation process, making the production process more complicated and the cost correspondingly increased.

[0005] More importantly, it is difficult to accurately control the bonding quality and performance gradient between layers of the multi-layer coating structure during the preparation process. The uneven bonding force between the layers may cause the coating to peel off and delaminate during use, making it impossible to effectively guarantee the quality of the gradient layer. Once there is a problem with the coating, it will directly affect the lubrication performance of the sliding bearing, resulting in increased friction and increased wear, thereby shortening the service life of the sliding bearing and reducing the reliability and operating efficiency of wind power equipment.

[0006] This series of problems seriously restricts the further development of wind turbine sliding bearing lubrication technology. An innovative solution is urgently needed to improve the lubrication performance of wind turbine sliding bearings and increase their reliability and service life under complex working conditions. Summary of the invention

[0007] The present invention aims to provide a coated copper-based composite coating material, a preparation process and an application thereof, so as to solve the technical problems of poor self-lubricating performance and low bonding strength of existing sliding bearings in the wind power field.

[0008] In order to achieve the above object, the present invention adopts the following technical scheme:

[0009] A self-lubricating material comprises the following components by mass fraction: 60-80% of aluminum bronze or tin bronze powder and 20-40% of lubricating phase, wherein the lubricating phase is a mixture of at least two powders of graphite, polyphenylene ester, bentonite, CaF2 and MoS2.

[0010] Preferably, it comprises 60% aluminum bronze powder and 40% graphite and CaF2 mixed powder, wherein the graphite content in the mixed powder is 40-60% and the remainder is CaF2.

[0011] Preferably, it comprises 50% tin bronze powder and 50% mixed powder of polyphenylene ester, CaF2 and MoS2, wherein the content of polyphenylene ester in the mixed powder is 30-50%, the content of CaF2 is 10-20%, and the balance is MoS2.

[0012] Preferably, it comprises 70% aluminum bronze powder, 30% graphite, polyphenylene ester, bentonite and CaF2 mixed powder, wherein the graphite content of the mixed powder is 30-50%, the polyphenylene ester content is 20-30%, the bentonite content is 10-15%, and the balance is MoS2.

[0013] The present invention also provides a method for preparing a coated copper-based composite powder, using a self-lubricating material as a substrate, comprising the following steps:

[0014] S1. Prepare copper-based composite powder by ball milling process, wherein the mass percentage of copper-based powder to lubricating phase is 10:1-15:1;

[0015] S2, preparing copper-based composite spherical powder: preparing a slurry from the composite powder in step 1, and grinding to obtain a uniformly dispersed suspension slurry; sending the suspension slurry to a spray drying tower for spray drying, the air inlet temperature of the drying tower is 100-200° C., to obtain agglomerated spherical powder; then drying the agglomerated powder, keeping it warm for 5-10 hours, sieving 100-150 μm powder, to obtain a copper-based composite spherical powder;

[0016] S3. Preparation of nickel-coated copper-based composite spherical powder: coating the composite powder of copper-based alloy and lubricating phase by chemical plating to obtain nickel-coated copper-based composite spherical powder.

[0017] Preferably, the copper-based composite powder obtained in step 1 is spherical, and the powder particle size is 90-120 μm. When the powder particle size is controlled within this range, the powder fluidity and solubility are optimal, which is convenient for improving the quality of subsequent laser cladding.

[0018] Preferably, the nickel-coated copper-based composite spherical powder obtained in step 3 has a coating layer with a thickness of 2-5 um.

[0019] A coated copper-based composite coating material is obtained by adopting the above preparation method.

[0020] The present invention also provides a preparation process of a clad copper-based composite coating material, which uses ultra-high-speed laser cladding to clad the composite coating material onto the surface of a substrate to form a composite coating, comprising the following steps:

[0021] S1, performing rough grinding and fine grinding on the area to be clad of the substrate to obtain a pretreated substrate;

[0022] S2. Use nickel-coated copper-based composite spherical powder to perform ultra-high-speed laser cladding on the pretreated substrate in step 1 to form a nickel-based wear-resistant self-lubricating coating; wherein the process parameters of ultra-high-speed laser cladding are: nitrogen or argon is used as powder feeding gas and protective gas, coaxial powder feeding is used, laser power is 1-5kW, spot diameter is 1.5-4.5mm, cladding line speed is 10-40m / min, powder feeding rate is 20-50g / min, and powder feeding gas flow rate is 10-15L / min;

[0023] S3. The cladding layer is machined and the surface roughness Ra of the coating is 0.8-1.6.

[0024] Preferably, the thickness of the nickel-based wear-resistant self-lubricating coating prepared in step 2 is 1.5 mm to 1.8 mm. When the thickness of the coating exceeds 1.8 mm, the preparation cost will be increased on the one hand, and the coating will be prone to cracking and peeling on the other hand.

[0025] The present invention also provides an application of a coated copper-based composite coating material, which is applied in the field of wind power and is clad on the surface of a sliding bearing to form a wear-resistant self-lubricating coating.

[0026] Invention concept:

[0027] In the field of wind power, sliding bearings have the advantages of low cost and high reliability compared to rolling bearings. However, their high reliability is closely related to the self-lubricating property of sliding bearings. In order to ensure the self-lubricating property of sliding bearings, it is currently common to prepare a copper-based alloy coating or add a polymer lubricating layer on the surface of the sliding bearing; the polymer lubricating layer mainly utilizes the good lubrication properties of the polymer material itself to reduce the friction coefficient. The molecular chain structure of the polymer material enables it to form a transfer film on the surface of the friction pair during the friction process. This transfer film can effectively separate the two friction surfaces and reduce direct contact between metals, thereby reducing friction and wear; the lubricating effect of the polymer lubricating layer is relatively stable, but the physical and chemical properties of the polymer material and the metal bearing surface are very different, the bonding force is limited, and under harsh working conditions such as high temperature and high load, the polymer lubricating layer is prone to aging, wear, and shedding, which leads to a decrease in bonding force.

[0028] Therefore, the more innovative solution at present is to add a lubricating phase to the copper-based composite powder. The copper-based alloy coating itself has certain metallic properties, which makes it easier to dissipate the heat generated during the friction process and avoid local overheating. At the same time, the copper-based alloy coating has good mechanical properties and high bonding strength, and can withstand higher loads. The lubricating phase can still play a friction-reducing role under high loads. Compared with copper-based alloy coatings or polymer lubricating layers, adding a lubricating phase to copper-based composite powders has multiple advantages such as high bonding strength and good lubrication properties.

[0029] Publication number CN116752076A discloses a method of adding lubricating phase and wear-resistant phase to copper-based powder to improve the self-lubricity and anti-friction performance of metal parts surface. It provides a wear-resistant self-lubricating material, a wear-resistant self-lubricating composite coating and its preparation method and mechanical metal parts, which include the following components: 10% to 20% nickel-coated graphite powder; 10% to 20% spherical alumina powder; the balance is copper-aluminum alloy powder. The invention can form a metal-based wear-resistant self-lubricating composite coating with good self-lubricity, anti-friction performance and large thickness on the surface of metal parts of mechanical equipment / equipment.

[0030] However, the application of the above technology to the sliding bearing in the wind power field of the present invention still has the following technical problems:

[0031] 1. Low bonding strength: This technology uses a plasma spraying process, and its maximum bonding strength is only about 35MPa. The minimum bonding strength required in the wind power field is 100MPa. Therefore, the existing technology cannot be used for the preparation of self-lubricating coatings on the surface of wind power sliding bearings.

[0032] 2. Wear of the wear-resistant phase spherical alumina on the sliding bearing: The low-speed and heavy-load service conditions in the wind power field lead to wear of the surface coating of the sliding bearing, resulting in the shedding of the hard wear-resistant phase of alumina. Once the hard wear-resistant phase falls off, it will cause secondary scratches on the surface of the sliding bearing, making the sliding bearing at risk of locking.

[0033] 3. Poor lubrication effect: There is only one lubricating phase, graphite. In the service environment of wind power, when the operating temperature rises, the graphite lubricating phase is prone to decomposition and the service life is reduced.

[0034] In summary, the inventors have conducted extensive research on the formula of existing copper-based composite coating materials, coating material preparation methods, and coating preparation methods, and have developed a coated copper-based composite coating with high lubricity, high bonding strength, and long service life; wherein, the friction coefficient can be as low as 0.15, and the bonding strength can be as high as 250MPa. After use and experimental verification, the service life is doubled, and no problems such as coating peeling occurred during service.

[0035] Technical principles and beneficial effects:

[0036] 1. Multi-component lubrication and synergistic lubrication:

[0037] In the preparation of copper-based composite powder, a variety of lubricating phases are selected, such as graphite, polyphenylene ester, bentonite, CaF2 or two of MoS2, which can achieve complementary characteristics of different lubricating phases. Graphite has a layered structure, the interlayer force is weak, and it is easy to slide during the friction process, thus playing a friction-reducing role; polyphenylene ester has good high temperature resistance and low friction coefficient, and can maintain stable lubrication performance under high temperature conditions; bentonite has adsorption and expansion properties, and can form an adsorption film on the friction surface to enhance the lubrication effect; CaF2 and MoS2 have excellent solid lubrication properties, and can effectively reduce the friction coefficient under harsh conditions such as high load and high temperature. The characteristics of these different lubricating phases complement each other. When they coexist in the coating, they can play their respective advantages under different operating conditions (such as temperature changes, load changes, etc.) to form a synergistic lubrication effect.

[0038] Moreover, the various lubricating phases are not simply mixed in the coating, but are evenly dispersed through processes such as ball milling to form a composite lubrication system. During the friction process, as the friction surface wears and the temperature changes, different lubricating phases can play a role in sequence or simultaneously; for example, in the initial stage, the layered structure of graphite can first provide a friction reduction effect. As the temperature rises, the high-temperature lubrication performance of polyphenylene ester begins to play a leading role, while CaF2 and MoS2 take on the main load-bearing and lubrication tasks in the high-load area. The adsorption film of bentonite helps to maintain the stability of the entire lubrication system, thereby achieving synergistic lubrication and significantly improving the self-lubricating property of the coating.

[0039] 2. Reduce coating hardness:

[0040] Most of the above-mentioned lubricating phases have relatively low hardness. For example, graphite is soft in texture. When it is evenly distributed in the coating as fine particles, it can reduce the overall hardness of the coating to a certain extent. When the coating is subjected to external force, these soft lubricating phases can deform and flow to a certain extent, absorbing part of the energy and avoiding brittle fracture or severe wear of the coating due to excessive hardness.

[0041] Compared with traditional high-hardness coatings, the multi-component lubricating phase coating in this technology has less impact on the hardness of the substrate when combined with the substrate due to its own lower hardness. During the friction process, the hardness difference between the coating and the substrate is relatively small, which helps to reduce coating peeling or substrate wear caused by hardness mismatch, thereby improving the overall collaborative working performance of the coating and the substrate, and further ensuring the durability of the lubrication effect.

[0042] 3. Copper-based alloy powder encapsulates the lubricating phase to avoid decomposition of the lubricating phase:

[0043] In the process of preparing nickel-clad copper-based composite spherical powder, the copper-based composite spherical powder first formed wraps the lubricating phase inside. This coating structure plays a role of physical isolation for the lubricating phase, thereby reducing its direct contact with the external high-temperature environment during the subsequent ultra-high-speed laser cladding process. The high temperature and energy generated during the laser cladding process mainly act on the copper-based alloy powder and the outer nickel layer, while the internal lubricating phase is subjected to relatively little thermal shock, thereby effectively avoiding the decomposition of the lubricating phase due to high temperature, which is beneficial to ensuring the performance of the lubricating phase.

[0044] In addition, the copper-based alloy powder and the nickel layer have certain thermal conductivity, but their heat conduction speed is relatively slow compared to direct exposure to the laser beam; when the laser energy is transferred to the coating structure, the copper-based alloy powder and the nickel layer will absorb and disperse part of the heat, slowing down the transfer of heat to the internal lubricating phase, allowing the lubricating phase to exist in a relatively low temperature environment, reducing the possibility of the lubricating phase reaching the decomposition temperature.

[0045] Finally, the outer nickel layer not only has good wear resistance, but also has a certain chemical stability; during the laser cladding process, the nickel layer can prevent oxidizing substances such as oxygen in the air from contacting the internal lubricating phase, avoiding chemical reactions such as oxidation and decomposition of the lubricating phase. At the same time, the presence of the nickel layer changes the chemical environment inside the cladding structure, allowing the lubricating phase to be preserved in a relatively stable chemical atmosphere, further improving the stability of the lubricating phase during high-temperature cladding.

[0046] 4. Ultra-high-speed laser cladding technology is beneficial to reduce the thermal impact on the substrate:

[0047] On the one hand, the cladding line speed of ultra-high-speed laser cladding technology reaches 10-40m / min, which is much faster than traditional laser cladding, thus improving the cladding efficiency. During the cladding process, the laser acts on the substrate surface and powder for a very short time, and the energy input per unit area is completed in a short time; this limits the amount of heat absorbed by the substrate in a short time, and there is no time to conduct a large amount of heat to the inside of the substrate, thereby reducing heat accumulation and reducing the thermal impact on the substrate.

[0048] On the other hand, due to the fast cladding speed, the clad coating quickly leaves the laser action area and enters the surrounding environment for rapid cooling; this rapid cooling process enables the substrate to quickly return to a lower temperature after being heated, reducing the changes in the substrate structure caused by long-term high temperature (such as grain growth, phase change, etc.), which is beneficial to maintaining the original properties of the substrate, such as strength and hardness. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a schematic diagram of the bonding strength sample of the copper-based composite coating of the present invention;

[0050] Figure 2 This is a cross-sectional morphology diagram of the copper-based composite coating in Experimental Example 1# of the present invention;

[0051] Figure 3 This is the friction coefficient curve after dry friction between the copper-based composite coating of Experimental Example 1 of the present invention and the Ф3mm GCr15 steel ball. DETAILED DESCRIPTION

[0052] The present invention provides a coated copper-based composite coating material and a preparation process thereof. Compared with the prior art, a multi-component lubricating phase is used to play a synergistic lubricating role, significantly improve the self-lubricating property of the coating, and reduce the hardness of the coating; the lubricating phase is coated with copper-based alloy powder to avoid the decomposition of the lubricating phase during ultra-high-speed laser cladding. That is, by optimizing the coating material formula, preparation method and ultra-high-speed laser cladding, it can be ensured that the bonding strength meets the standard or even far exceeds the standard requirements, and the decomposition of the lubricating phase during the cladding process can be avoided, thereby ensuring the functionality of the lubricating phase and significantly improving the service life of the coating.

[0053] A self-lubricating material comprises the following components by mass fraction: 60-80% of aluminum bronze or tin bronze powder and 20-40% of lubricating phase, wherein the lubricating phase is a mixture of at least two powders of graphite, polyphenylene ester, bentonite, CaF2 and MoS2.

[0054] Specifically, the combination of the components of the self-lubricating material in the present invention is shown in Table 1.

[0055] Table 1: Mass composition of self-lubricating materials (mass percentage, wt.%)

[0056]

[0057]

[0058] A method for preparing a coated copper-based composite powder comprises the following preparation steps:

[0059] Step 1: Preparation of copper-based composite powder:

[0060] Weigh 60-80% by mass of aluminum bronze (copper (Cu), aluminum (Al), iron (Fe), nickel (Ni)) or tin bronze powder (CuSn4), 20-40% by mass of graphite, polyphenylene ester, bentonite, CaF2 or MoS2 mixed powder of two kinds thereof, and place them in a ball mill with a ball-to-material ratio of 10:1-15:1 by mass percentage for ball milling and mixing. During mixing, 2-4% by mass of stearic acid is added as a process control agent, the ball milling speed is 200-800rpm, the ball milling time is 24-96h, and finally a copper-based composite powder is formed; the copper-based composite powder prepared in the present invention is spherical, and the powder particle size is 90-120μm.

[0061] Step 2: Preparation of copper-based composite spherical powder:

[0062] Add 1-5% of the total weight of a binder and 30-70% of deionized water to the copper-based composite powder prepared in step 1, mix and stir to form a slurry, and grind to obtain a uniformly dispersed suspension slurry. Specifically, the binder of the present invention uses polyethylene glycol; send the suspension slurry to a spray drying tower for spray drying, the air inlet temperature of the drying tower is 100-200° C., to form an agglomerated powder; dry the prepared agglomerated powder in a drying oven at 100-150° C. for 5-10 hours, and sieve out 100-150 μm powder to obtain a spherical copper-based composite spherical powder.

[0063] Step 3: Preparation of nickel-coated copper-based composite spherical powder:

[0064] The spherical copper-based composite spherical powder obtained in step 2 is soaked in a KOH solution with a pH value of 8-10 for 2-10 minutes, and the present invention preferably uses a KOH solution with a pH value of 8 for soaking for 2 minutes; the powder is filtered and added to a zinc sulfate solution, soaked for 10-60 minutes, and then filtered again, preferably soaked for 10 minutes; wherein 2-20wt% of tartaric acid is added to the zinc sulfate solution, and the preferred addition amount is 2.

[0065] A nickel sulfate solution is added to a reaction vessel, wherein the nickel ion concentration of the solution is 20-100 g / L, preferably the nickel ion concentration is 20 g / L, and spherical copper-based powder is added during the heating and stirring of the solution. When the solution is heated to 50-90° C., sodium hypophosphite is added at a rate of 1-2 L / min to adjust the pH value of the solution to 5-7; preferably, when the solution is heated to 50° C., sodium hypophosphite is added at a rate of 1 L / min to adjust the pH value of the solution to 7.

[0066] After the solution becomes colorless and transparent, stop adding sodium hypophosphite, continue to react at 300-600°C for 30-60min, fully stir during the reaction, and the speed of the stirring rotor is 50-80rpm to promote the reaction; when the speed is lower than 50rpm, the reaction is not sufficient, and when the speed is higher than 80rpm, the reaction solution is easy to overflow; after the above reaction time, a nickel-coated copper-based composite spherical powder is obtained, wherein the thickness of the coating layer is 2-5um; then the powder is filtered and dried, and hydrogen is introduced for reduction.

[0067] The above preparation method is used to prepare the copper-based alloy and lubricating phase in each combination in Table 1 into a coated copper-based composite powder. The preparation steps and process parameters are shown in Table 2.

[0068] Table 2: Preparation process parameters corresponding to various lubricating material combinations

[0069]

[0070]

[0071] The present invention also provides a coated copper-based composite coating material, which is obtained by the preparation method of steps 1-3 above.

[0072] The present invention also provides a preparation process of a clad copper-based composite coating material, which uses ultra-high-speed laser cladding to clad the clad copper-based composite coating material onto the surface of a substrate to form a composite coating, comprising the following steps:

[0073] Step 1: performing rough grinding and fine grinding on the area to be clad of the substrate to obtain a pretreated substrate;

[0074] Step 2: Use nickel-coated copper-based composite spherical powder to perform ultra-high-speed laser cladding on the pre-treated substrate in step 1 to form a nickel-based wear-resistant self-lubricating coating. The process parameters of ultra-high-speed laser cladding are: nitrogen or argon is used as powder feeding gas and protective gas, coaxial powder feeding is used, laser power is 1-5kW, spot diameter is 1.5-4.5mm, cladding line speed is 10-40m / min, powder feeding rate is 20-50g / min, and powder feeding gas flow rate is 10-15L / min.

[0075] Specifically, in actual use, the laser power can be 5 kW, the spot diameter can be 1.5 mm, the cladding line speed can be 10 m / min, the powder feeding rate can be 20 g / min, and the powder feeding gas flow rate can be 10 L / min; or the laser power can be 1 kW, the spot diameter can be 4.5 mm, the cladding line speed can be 40 m / min, the powder feeding rate can be 50 g / min, and the powder feeding gas flow rate can be 15 L / min; the present invention preferably uses the former process parameters for cladding.

[0076] Step 3: machining the cladding layer, the coating surface roughness Ra is 0.8-1.6. Specifically, the present invention can select Ra as 0.8 or 1.6, preferably Ra is 0.8.

[0077] The present invention also provides an application of a coated copper-based composite coating material, which is used in the field of wind power and is clad on the surface of a sliding bearing to form a wear-resistant self-lubricating coating with a coating thickness of 1.5mm-1.8mm; the composite coating significantly improves the self-lubricating performance, reliability and service life of the sliding bearing.

[0078] By using the above-mentioned cladding process, the coated copper-based composite material obtained in Table 2 was clad on the surface of the substrate to form a lubricating coating (the coating thickness was 1.5 mm-1.8 mm), and the various properties of the coating were tested. The experimental results are shown in Table 3.

[0079] Table 3: Performance indicators of copper-based composite coatings under various combinations and processing conditions

[0080]

[0081]

[0082] Specifically, the test methods for each indicator in Table 3 are as follows

[0083] (1) Test method for average friction coefficient: The friction test is a reciprocating dry friction test with a reciprocating amplitude of 5 mm, a reciprocating speed of 15 mm / min, a test time of 60 min, and a load of 1000 g.

[0084] (2) Test method for bonding strength: Use wire cutting to process non-standard plate-shaped tensile specimens, the specific dimensions of which are as follows: Figure 1 As shown. Then, 400#, 800# and 1200# metallographic water sandpapers were used to polish the surface of the plate-shaped tensile specimen, especially the arc transition section. The final surface roughness of the specimen was ~0.5μm. Finally, a special fixture was used to fix the specimen, and the strength of the specimen was tested on a universal mechanical testing machine. The tensile speed of the specimen was 0.5mm·min -1. Test at least 5 specimens and calculate their average value as the strength of the specimen.

[0085] (3) Wear rate test method: After the wear test, the wear scars were obtained by laser confocal microscopy, and the wear area S of the wear scars was integrated and calculated using Origin software. Then, the wear rate of the material was estimated according to Formula 1.

[0086]

[0087] In formula 1, Δv is the wear volume of the material, F is the pressure during the wear process, and L is the friction distance, where Δv is obtained by solving the cross-sectional area S of the wear scar and the wear radius R.

[0088] Among them, in the wind power field where the present invention is applied, the basic technical indicators for the application requirements of the sliding bearing lubricating coating are as follows: bonding strength is 100 MPa, average friction coefficient is 0.15, and hardness is 150 HV.

[0089] The following conclusions can be drawn from Table 1-3:

[0090] 1. When the self-lubricating material adopts combination 1, according to Examples 1#-2#, the bonding strength of the lubricating coating is greater than 200MPa, the average friction coefficient is less than 0.21, and the wear rate and hardness of the coating are both in a relatively ideal state; and the lubricating phase is evenly distributed, and no decomposition occurs after cladding, and the service life of the coating is relatively long. This is mainly due to the synergistic effect of the lubricating phase, and the formation of spherical powder with a particle size of 90-120um in the preparation process, and the chemical nickel plating of the spherical powder to control the coating thickness to 2-5um. This coating structure not only protects the lubricating phase from high-temperature decomposition, but also makes the coating and the substrate more tightly bonded, thereby improving the bonding strength.

[0091] According to experimental examples 3-5#, the bonding strength and average friction coefficient of the lubricating coating are greatly reduced, the wear is large, and the hardness is high. The bonding strength of experimental examples 3# and 5# is lower than the minimum bonding strength requirement of 100MPa in the wind power field. The main reason is that the powder prepared in experimental example 3# is flat. Compared with spherical powder, the fluidity and filling property of flat powder are poor. It cannot be evenly distributed on the surface of the substrate during the cladding process, resulting in uneven coating structure, affecting the bonding strength between the coating and the substrate (only 75MPa); and the uneven coating structure also makes the local force uneven during the friction process, aggravates the wear, and increases the wear rate. At the same time, the hardness distribution is uneven, and the overall hardness is high.

[0092] 2. When the self-lubricating material adopts combination 2-5, according to experimental examples 6#-9#, the bonding strength of the lubricating coating is increased by about 2 times compared with the basic indicator 100MPa. The bonding strength is increased, and it is not easy to fall off during use, which increases the service life of the coating; and due to the synergistic effect of multiple lubricating phases, the friction coefficient is effectively reduced, the wear is reduced, and the wear rate is kept at a low level; at the same time, the presence of multiple lubricating phases makes the coating hardness moderate, which not only ensures the wear resistance of the coating, but also does not cause brittle fracture or substrate wear due to excessive hardness.

[0093] 2. When the self-lubricating material adopts the control 1-4, according to the experimental examples 10#-13#, the lubricating phase distribution uniformity of the lubricating coating after cladding is poor, and partial decomposition occurs; the bonding strength of the coating is greatly reduced, which is lower than the application requirements; the friction coefficient, wear rate and hardness increase, which are all greater than the application requirements and cannot be directly used in the wind power field.

[0094] The main reasons are:

[0095] (1) In the combination, the lubricating phase is single and the proportion is inappropriate: Control 1 contains only 20% graphite as the lubricating phase. Under the complex working conditions in the wind power field, a single lubricating phase cannot meet multiple requirements. When the operating temperature rises, the graphite lubricating phase is prone to decomposition, resulting in a decrease in lubrication effect, an increase in friction coefficient (0.38), and increased wear. Control 3 contains 30% bentonite as the lubricating phase. Although bentonite has adsorption and expansion properties, it cannot provide sufficient lubrication and load-bearing capacity when used alone in the coating, affecting the comprehensive performance of the coating.

[0096] (2) Powder preparation and processing technology issues: In the preparation process of controls 1 and 3, the ball milling process resulted in insufficient powder mixing, and the temperature of the air inlet of the drying tower was high and the insulation time was long, resulting in the powder being flat, affecting the density and uniformity of the coating and reducing the bonding strength. In controls 2 and 4, the chemical nickel plating reaction temperature was high and the time was long, resulting in the coating layer being too thick (10um for control 2 and 15um for control 4), which led to stress concentration and affected the stress transfer between the coating and the substrate, greatly reducing the bonding strength. In addition, the uniformity of the lubricating phase distribution in the control combination was poor, and partial decomposition was prone to occur during the cladding process, further deteriorating the coating performance and making it unable to meet the requirements for coatings in the wind power field.

[0097] In summary, the composition of the lubricating phase is crucial to the performance of the coating. A combination of multiple and reasonably proportioned lubricating phases can achieve synergistic lubrication, reduce the friction coefficient and wear rate, optimize the hardness, and improve the stability of the coating, thereby extending the service life. The ball milling process (ball-to-material ratio, rotation speed, time), powder shape control, and chemical nickel plating process (coating thickness and related parameters) in the preparation process have a significant impact on the performance of the coating. In particular, when the thickness of the powder coating is too high, the performance of the coating is significantly reduced. Reasonable process parameters can ensure the uniform distribution of the lubricating phase, form a good coating structure, improve the bonding strength between the coating and the substrate, and ensure the reliability of the coating during use.

[0098] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A self-lubricating material, characterized in that: The invention comprises the following components by mass fraction: 60-80% of aluminum bronze or tin bronze powder and 20-40% of lubricating phase, wherein the lubricating phase is a mixture of at least two powders of graphite, polyphenylene ester, bentonite, CaF2 and MoS2.

2. A self-lubricating material according to claim 1, characterized in that: The invention comprises 60% aluminum bronze powder and 40% graphite and CaF2 mixed powder, wherein the content of graphite in the mixed powder is 40-60% and the balance is CaF2.

3. A self-lubricating material according to claim 1, characterized in that: The invention comprises 50% tin bronze powder and 50% mixed powder of polyphenylene ester, CaF2 and MoS2, wherein the content of polyphenylene ester in the mixed powder is 30-50%, the content of CaF2 is 10-20% and the balance is MoS2.

4. A self-lubricating material according to claim 1, characterized in that: The invention comprises 70% aluminum bronze powder, 30% graphite, polyphenylene ester, bentonite and CaF2 mixed powder, wherein the graphite content in the mixed powder is 30-50%, the polyphenylene ester content is 20-30%, the bentonite content is 10-15% and the balance is MoS2.

5. A method for preparing a coated copper-based composite powder, using the self-lubricating material according to any one of claims 1 to 4 as a substrate, characterized in that: The steps include: S1. Prepare copper-based composite powder by ball milling process, wherein the mass percentage of copper-based powder to lubricating phase is 10:1-15:1; S2, preparing copper-based composite spherical powder: preparing a slurry from the composite powder in step 1, and grinding to obtain a uniformly dispersed suspension slurry; sending the suspension slurry to a spray drying tower for spray drying, the air inlet temperature of the drying tower is 100-200° C., to obtain agglomerated spherical powder; then drying the agglomerated powder, keeping it warm for 5-10 hours, sieving 100-150 μm powder, to obtain a copper-based composite spherical powder; S3. Preparation of nickel-coated copper-based composite spherical powder: coating the composite powder of copper-based alloy and lubricating phase by chemical plating to obtain nickel-coated copper-based composite spherical powder.

6. The method for preparing a coated copper-based composite powder according to claim 5, characterized in that: The copper-based composite powder obtained in step 1 is spherical, and the powder particle size is 90-120 μm.

7. The method for preparing a coated copper-based composite powder according to claim 6, characterized in that: The nickel-coated copper-based composite spherical powder prepared in step 3 has a coating layer with a thickness of 2-5 um.

8. A coated copper-based composite coating material, characterized in that: The preparation method according to claim 7 is used to obtain the 9. A process for preparing a clad copper-based composite coating material, wherein the composite coating material according to claim 8 is clad onto the surface of a substrate by ultra-high-speed laser cladding to form a composite coating, characterized in that: The following steps are included: S1, performing rough grinding and fine grinding on the area to be clad of the substrate to obtain a pretreated substrate; S2. Use nickel-coated copper-based composite spherical powder to perform ultra-high-speed laser cladding on the pretreated substrate in step 1 to form a nickel-based wear-resistant self-lubricating coating; wherein the process parameters of ultra-high-speed laser cladding are: nitrogen or argon is used as powder feeding gas and protective gas, coaxial powder feeding is used, laser power is 1-5kW, spot diameter is 1.5-4.5mm, cladding line speed is 10-40m / min, powder feeding rate is 20-50g / min, and powder feeding gas flow rate is 10-15L / min; S3. The cladding layer is machined and the surface roughness Ra of the coating is 0.8-1.

6.

10. The process for preparing a coated copper-based composite coating material according to claim 9, characterized in that: The nickel-based wear-resistant self-lubricating coating prepared in step 2 has a coating thickness of 1.5 mm to 1.8 mm.

Citation Information

Patent Citations

  • Solid lubricating high-temperature anti-wearing powder composition and preparation method of compound coating of composition

    CN102836996A

  • Copper-based anti-abrasion anti-impact bi-metal composite material and preparation method thereof

    CN105665695A

  • Wide-temperature-range wear-resistant self-lubricating coating as well as preparation method and application thereof

    CN116200695A

  • Impact-resistant and wear-resistant copper plate material for laser composite manufacturing of precision forging machine and preparation method of impact-resistant and wear-resistant copper plate material

    CN117245087A

  • Bearing surface coating processing method and application thereof

    CN117431536A